The Community Structure of Sea Urchins (Echinoidea) in the Intertidal Zone of Thomas Beach, Uluwatu - Gilang Caraka; I Wayan Arthana; Ni Made Ernawati (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
Thomas Beach, located in Uluwatu, Province of Bali, is a rocky shore inhabited by sea urchins. The research aims to discover the habitat characteristics and community structure of sea urchins (Echinoidea) in the intertidal zone of Thomas Beach. Data collection was conducted from April to May 2023 during the lowest tide. A quantitative method with modified line transects was used for data collection. Data collected included the number and species of sea urchins, water quality parameters (temperature, salinity, pH, dissolved oxygen, water clarity, and depth), and substrate types. Data were analyzed using Microsoft Excel, including individual density, diversity index, uniformity index, and dominance index. The research findings revealed five species of sea urchins: Echinotrix calamaris, Echinometra oblonga, Echinometra mathaei, Tripneustes gratilla, and Stomopneustes variolaris. The highest density of sea urchins was found in E. oblonga (16.91 ind/m2). The diversity index values ranged from 0.4936 to 0.8721, indicating a low level of diversity. The uniformity index values ranged from 0.4493 to 0.784, suggesting the community is relatively unstable. The dominance index values ranged from 0.5036 to 0.7166, indicating a moderate level of dominance. The aquatic habitat characteristics, based on the research findings, it was determined that a temperature of 30℃, salinity ranging from 31.77 to 32.76, pH of 8, dissolved oxygen (DO) of 5 mg/l, water clarity of 100%, and a depth ranging from 8.4 to 33.93 cm. The substrate type was rocky at station 1, sandy with seagrass at station 2, and rocky sandy at station 3.